Role of methyl prednisolone in reducing mortality and morbidity in hair dye poisoning - A., Akhtar; B. D., Verma (International Journal of Advances in Medicine, 2017)
Background: Hair dye containing paraphenylenediamine (PPD) is widely used in India because of its free availability and low cost. PPD produces local as well as systemic toxic effects when applied topically and/or ingested. This study was undertaken to find the role of methyl prednisolone in reducing mortality and morbidity in hair poisoning and to study the cardiac complications of hair dye poisoning. Methods: The present study was carried out among 1000 cases admitted in the Department of Medicine, MLB Medical College, Jhansi with history/characteristic and clinical features of hair dye poisoning. The complication and mortality profile was studied. Statistical significance was drawn with the help of Microsoft excel 2003. Results: Mortality in acute hair dye poisoning cases was 23.20%. Majority of deaths (50.04%) occurred within 24 hours of hair dye ingestion and were because of asphyxia and respiratory failure. Mortality in 44.96% cases was after 24 hours and were mainly due to renal failure and its related complications hyperkalaemia and cardiac complication. Lower mortality was observed in group A (8.40%) as compared to group B (8.0%) and C (4.0%) in association with ST and T wave changes. Conclusions: PPD is available quite freely and used extensively. Awareness regarding its poisonous effects should be increased among the medical health care workers.